Maximum likelihood source localisation in wireless sensor network using particle swarm optimisation. (22nd April 2013) - Panigrahi, T.; Panda, G.; Majhi, B.
Direction–Of–Arrival (DOA) estimation in wireless sensor network is an important problem. Decentralised approach using antenna arrays at each node or sensor arrays at different positions are used to localise the sources. In this paper we proposed a centralised method where every node will participate in bearing estimation to achieve best resolution with minimum computation. The DOA is obtained by optimising ML function formed by a random array with all the nodes globally. A Particle Swarm Optimisation (PSO) based solution is proposed here to compute DOA. Simulation results confirm the advantages of PSO over most analysed multiple signal classification (MUSIC) algorithms.